Improving Students' Writing Skill in Writing Descriptive Text using Brainstorming Plus Webbing Techniques - Dhananjaya, Putu Aditya; Karima, Festi Himatu; Egar, Ngasbun (Journal of Nusantara Education, 2024)
Improving students' writing skills is the most important thing in their academic journey, yet it often poses some difficulties. This research was aimed to explore into this critical area, specifically focusing on improving students' ability in writing descriptive text. Moreover, it seeks to determine the effectiveness of applying either one or two writing techniques in order to achieve this objective.The study was conducted among 25 students in the VIII H class at SMP Negeri 29 Semarang. To measure the impact of different writing techniques, pre-tests and post-tests were conducted as research instrument. The control group were instructed to utilize the brainstorming technique exclusively, while the experimental group were treated by receiving instruction using both brainstorming and webbing techniques. Upon analysis of the collected data, the results showed a significant difference in students' achievement in writing descriptive text between the two groups. Specifically, the t-test value was calculated of 8.47 meaning that it surpassed the critical t-table value of 2.069 at a 5%. This differences underscores the acceptance of the alternative hypothesis (Ha), indicating the efficiency of the brainstorming plus webbing techniques in developing some improvements in students' descriptive writing skills compared to just utilizing brainstorming alone. These findings hold deep implications for academical practices aimed at improving students' writing abilities. By explaining the effectiveness of utilizing multiple teaching strategies, this research not only contributes to the academic conversation on effective teaching techniques but also provides valuable insights for educators seeking to level up their teaching approaches for the benefit of their students' academic development. _______________________________________________________________________________________ Meningkatkan kemampuan menulis siswa merupakan hal yang sangat penting dalam tahapan  akademis mereka, namun sering kali merupakan tantangan yang signifikan. Dalam penelitian ini, kami berusaha untuk menelusuri ruang lingkup ini, dengan fokus khusus pada meningkatkan kemampuan siswa dalam membuat dan menyusun teks deskriptif. Selain itu, penelitian ini bertujuan untuk menentukan efektivitas dari penggunaan satu atau dua teknik menulis dalam mencapai tujuan ini. Studi ini dilakukan dengan mengajak 25 siswa yang terdaftar di kelas VIII H di SMP Negeri 29 Semarang. Untuk menilai dampak pendekatan pengajaran yang berbeda, pre-test dan post-test dijadikan sebagai alat untuk mengukur nilai kemampuan siswa selama penelitian berlangsung. Kelompok kontrol atau control group menjalani pembelajaran hanya dengan menggunakan teknik brainstorming saja, sementara kelompok eksperimen atau experimental group menerima pembelajaran yang menggunakan pengabungan dari teknik brainstorming dan webbing. Setelah menganalisis data yang terkumpul dari pre-test dan post-test, hasilnya menunjukkan bahwa terdapat perbedaan yang signifikan dalam pencapaian siswa dalam menulis teks deskripsi antara kedua kelompok. Temuan ini memiliki implikasi yang mendalam bagi praktik pengajaran yang bertujuan meningkatkan kemampuan menulis siswa. Dengan menjelaskan efektivitas penggunaan berbagai strategi pengajaran, penelitian ini tidak hanya memberikan kontribusi pada diskusi ilmiah tentang metodologi pengajaran yang efektif tetapi juga memberikan wawasan berharga bagi pendidik yang ingin mengoptimalkan pendekatan pengajaran mereka demi kemajuan akademis siswa mereka.